2023
DOI: 10.1039/d2ee01634f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable formamidinium–caesium perovskite solar cells and modules from lead acetate-based precursors

Abstract: The control of the crystallization process of perovskite thin films to obtain a high-quality material is one of the most challenging aspects for upscaling perovskite solar cell (PSC) technology. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…However, the crystallization of MAPbI 3 perovskites is quite different from FACs-based mixed-cation lead mixed-halide perovskites, and only recently was chemistry suitably developed to create lead acetate-based precursors for these perovskites. 37 With the reporting of this recent development, we decided to extend the system to investigate the effect of chloride incorporation in lead acetate-based precursors on the film quality of a FACsbased WBG perovskite, namely, FA 0.83 Cs 0.17 Pb(I 0.8 Br 0.2 ) 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the crystallization of MAPbI 3 perovskites is quite different from FACs-based mixed-cation lead mixed-halide perovskites, and only recently was chemistry suitably developed to create lead acetate-based precursors for these perovskites. 37 With the reporting of this recent development, we decided to extend the system to investigate the effect of chloride incorporation in lead acetate-based precursors on the film quality of a FACsbased WBG perovskite, namely, FA 0.83 Cs 0.17 Pb(I 0.8 Br 0.2 ) 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Qing et al and Yalcinkaya et al , demonstrated that incorporating chloride into a PbAc 2 -based precursor solution improved the crystallization of the narrow bandgap perovskite MAPbI 3 by decreasing the evaporation rate of the methylammonium chloride (MACl) byproduct compared to methylammonium acetate (MAAc), resulting in enlarged grain sizes and reduced trap density. However, the crystallization of MAPbI 3 perovskites is quite different from FACs-based mixed-cation lead mixed-halide perovskites, and only recently was chemistry suitably developed to create lead acetate-based precursors for these perovskites . With the reporting of this recent development, we decided to extend the system to investigate the effect of chloride incorporation in lead acetate-based precursors on the film quality of a FACs-based WBG perovskite, namely, FA 0.83 Cs 0.17 Pb­(I 0.8 Br 0.2 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 31,32 ] Very recently, Zhao et al demonstrated efficient and stable 3D FA 0.83 Cs 0.17 Pb(I 0.9 Br 0.1 ) 3 perovskite solar cells and modules from PbAc 2 ‐based precursor using industrially scalable blade‐coating techniques in an ambient air environment. [ 33 ] Moreover, PbAc 2 can be easily produced from spent lead–acid batteries for lead recycling and low‐cost fabrication. [ 34 ] However, the lead sources for RPPs have been limited to lead halides, usage of nonhalide lead sources has rarely been investigated in RPPs to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%